The parables of Jesus as critique on food security systems for vulnerable households in urban townships - Van Eck, Ernest; Mashinini, Meshack Mandla (Hervormde teologiese studies, 2016)
A recent empirical study on food shortage in South African urban townships indicates thatfood shortage embodies multi-faceted aspects with broader social implications, such as thesense of personal dignity, the ability to openly associate with others and a loss of self-identity.It is argued that the parables of Jesus, when read as symbols of social transformation, providea critique on food insecurity systems in urban townships. It is proposed that the parables ofJesus serve as the conduits for a societal and perhaps ecclesial reorientation with regard to theconditions of hunger, in the light of the vision and values of the kingdom of God.